New ilp method based on γ-tubulin genes intron length polymorphism - Pirko, Ya.V.; Buy, D.D.; Postovoitova, A.S.; Rabokon, A.M.; Kalafat, L.O.; Blume, Ya.B. (Reports of the National Academy of Sciences of Ukraine, 2018)
A new marker system for the estimation of a genetic diversity based on the γ-tubulin genes intron length polymorphism is proposed. A pair of degenerate primers to γ-tubulin genes was developed based on the characteristics of their exon-intron structures. The simplicity and versatility of the marker system in the moleculargenetic analysis of plants are demonstrated on species and varieties of Arabidopsis thaliana, Linum usitatissimum, Solanum tuberosum, Oryza sativa, Triticum aestivum.